The Effects of Business Strategy (Prospector and Defender) on Business Performance with Entrepreneurial Orientation as Mediating Variable and Social Media Usage as Moderating Variable on MSME at Surabaya - Priscillia, Cynthia M.; Tjahjadi, Bambang; Wulani, Fenika (Advances in Social Sciences Research Journal, 2022)
Micro Small Medium Enterprise (MSME) had been acknowledged as one of the biggest drivers of the national economy. In order to achieve better performance, MSME must have a good strategy. The purpose of this study is to prove the influence of business strategy on business performance. This study uses prospector and defender strategy and also entrepreneurial orientation as a mediating variable and social media usage as a moderating variable. The respondent is 137 MSME under Surabaya Kriya Gallery Reborn Siola (one of MSME’s incubator that managed by the city government). The data was acquired using an online questionnaire and analysed using SmartPLS 3.0. The finding of this paper is business strategy (prospector and defender) confirmed to influence firm performance, with prospector having the higher value than defender. Entrepreneurial orientation is confirmed as a mediating variable but for defender strategy only. Social media usage is also confirmed as a moderating variable to overall business strategy, but this study found that there is no moderating effect if it is for prospector or defender. These findings contribute to adding more information about strategy (prospector and defender), entrepreneurial orientation and social media usage in a term of MSME performance. The future research can examine prospector and defender as a moderating variable or social media usage as an antecedent variable. Future research can conduct the research in one specific industry only instead of general industries.